A Person‐Oriented Analysis of Couple and Relationship Education. Issue 5 (December 2016) - DuPree, Devin G.; Whiting, Jason B.; Harris, Steven M.
Abstract : Couple and relationship education (CRE) has effectively improved communication and relationship satisfaction, but some question its effectiveness for couples who are at risk. Mixed findings may derive from focusing on aggregated sample results. This study explored the benefit of using a person‐oriented analysis for evaluating CRE program effectiveness with low‐income couples and individuals. Couple participants reported moderate improvement in communication and relationship satisfaction, but the magnitude of reported improvement varied for male participants from different ethnic groups. An outcomes‐focused cluster analysis showed that variance in reported improvement can be explained by pre‐workshop outcome measures, with couples starting in the middle range of scores reporting the most improvement. Similar patterns were found for individual participants. Researchers and practitioners should further investigate the use of person‐oriented methods in CRE program evaluation and the use of pre‐workshop assessments to adjust CRE interventions on the basis of the state of participants' relationships at intake.